The Qixiangzhan eruption, Changbaishan-Tianchi volcano, China/DPRK: new age constraints and their implications - Pan, Bo; DeSilva, Shanaka L.; Danišik, Martin; Schmitt, Axel Karl; Miggins, Daniel P. (Scientific reports, 2022)
Zircon double dating (ZDD) of comendite lava reveals an eruption age of 7.0 ± 0.9 ka for the Qixiangzhan eruption (QXZ), Changbaishan-Tianchi volcano, China/DPRK. This age is supported by new 40Ar/39Ar sanidine experiments and a previous age control from charcoal at the base of the QXZ. The revised age supports correlations with distal ash in Eastern China and Central Japan and establishes a significant (estimated at Volcanic Explosivity Index 5+) eruption that may provide a useful Holocene stratigraphic marker in East Asia. The new age indicates that the QXZ lava does not record a ca. 17 ka Hilina Pali/Tianchi geomagnetic field excursion but rather a heretofore unrecognized younger Holocene excursion at ca. 7-8 ka. Comparison between U-Th zircon crystallization and ZDD as well as 40Ar/39Ar sanidine ages indicates a protracted period of accumulation of the QXZ magma that extends from ca. 18 ka to the eruption age. This connotes an eruption that mixed remobilized early formed crystals (antecrysts) from prior stages of magma accumulation with crystals formed near the time of eruption. Based on these results, a recurrence rate of ca. 7-8 ka for the Changbaishan-Tianchi magma system is found over the last two major eruption cycles.
Gesehen am 23.03.2023